CELEBRITY ENDORSEMENT IN BUSINESS - Nabil Tarifi; Muhammad Khan; DUAA ALGHAMDI (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Companies globally regard celebrity endorsement as an effective advertising tool. Celebrity endorsement is important for brand awareness among the consumers, and it plays a significant role in customer’s purchase intention and the success of a business. Hence, this work was done to analyze the impact of celebrity endorsement in business at Saudi Arabia. The research aims to understand on how fame influences business especially in the context of celebrity endorsement among consumer in Saudi Arabia. This work was done based on quantitative method. Questionnaire was utilized for data collection. The number of samples of this study was 100 entrepreneurs in Jeddah, Saudi Arabia. The findings of this work has shown that majority of the respondents agree that the celebrity use their fame for advertising purpose. Furthermore, the findings have shown that majority of the respondents have bought products advertised by celebrities. In addition, 55% of the respondents have agreed that they will use celebrity endorsement for marketing products. Moreover, 75 % of the respondents agree that celebrity endorsement is effective for product and business marketing. Hence, it is concluded that celebrity endorsement has a positive influence on the success of a business.